Alkenylation of 1- and 2-Naphthols by Using Magnesium Alkylidene Carbenoids as Electrophilic Alkenylating Agents - Kimura, Tsutomu; Watanabe, Masaya; Kashiwamura, Gaku; Sakurada, Jo; Satoh, Tsuyoshi (Synthesis, 2013)
1- and 2-Naphthols were successfully alkenylated in a regioselective manner by treating the corresponding lithium 1- and 2-naphtholates with magnesium alkylidene carbenoids. The magnesium alkylidene carbenoids were generated in situ by a sulfoxide–magnesium exchange reaction of 1-chlorovinyl 4-tolyl sulfoxides with isopropylmagnesium chloride. The reaction of magnesium alkylidene carbenoids with lithium 2-naphtholates took place at the 1-position of the naphthyl ring to give 1-(alk-1-enyl)-2-naphthols in respectable yields. The alkenylation of 1-naphthols proceeded at the 2-position of the naphthol ring to give 2-(alk-1-enyl)-1-naphthols in yields of 56–67%. In contrast to the reaction of lithium naphtholates with magnesium alkylidene carbenoids, the reaction of lithium phenolates gave low yields of the corresponding alk-1-enyl aryl ethers.
Keywords: alkenation; phenols; carbenoids; sulfoxides; alkenes; arenes; organometallic reagents